Design of Analysis Platform for College Students' Physical Learning Effect Based on Data Mining Algorithm - Wang, Jinzhao (2023 IEEE International Conference on Integrated Circuits and Communication Systems (ICICACS), 2023)
The design of College Students' physics learning effect analysis platform based on data mining algorithm is the process of designing a computer program, which will automatically analyze the results from large databases to find patterns. The purpose of this study is to develop an analytical framework for assessing and improving the effectiveness of sports events, called dapt. Dapt aims to develop an analytical framework to provide information about students' learning effects by analyzing their performance in physical education classes. This framework should have three components: (1) data mining algorithm, (2) evaluation method, and (3) improvement. In this paper, the design of the platform for analyzing the effect of College Students' Physical Education Learning Based on data mining algorithm and the results obtained by the data mining algorithm are of positive help to teachers in diagnosing teaching problems and constructing characteristic teaching curriculum system.